The Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) scores in 961 Japanese volunteers. (9th November 2020) - Hosokawa, Takafumi; Tajika, Tsuyoshi; Suto, Morimichi; Chikuda, Hirotaka
Introduction: Patient-reported outcomes recently have been used to assess treatment outcomes. The Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) is a particularly convenient and useful tools. However, data on the normative values of Japanese population are lacking, so the present study was conducted to gather this information. Methods: We assessed 1098 volunteers over 18 years of age (363 men and 735 women, average 50 years old) who had not received upper limb treatment in a medical facility. These participants included our institution's staff, their family members, and the participants in the group meetings held by institution's staff. Their occupations were also examined. We divided occupations into nonmanual and manual labor. These factors of the participants were then analyzed to clarify which (if any) influenced the QuickDASH. Results: Valid answers were obtained from 961 subjects (87.5%). The median score was 2 (mean: 4.8) in the overall population, 0 (mean: 2.6) in men, and 2.5 (mean: 6.0) in women. The scores increased with age and were higher in women than in men. There were no significant differences by manual labor. Female sex and older age were identified as factors that influenced the QuickDASH score in the multiple regression analysis. There were high correlations among QuickDASH, work and sports/music scores. Conclusions: The present study provided QuickDASH scores for Japanese volunteers who had not received upper limb treatment in a medical facility. The scores were associated with older age and female sex. This study helps us to know the degree of potential upper limb impairment in the general population, and will help in populational strategies as primary and secondary preventive medicine for upper limb-related diseases.